Effects of sphingosylphosphorylcholine against oxidative stress and acute lung injury induced by pulmonary contusion in rats - Aksu, Burhan; Ayvaz, Suleyman; Aksu, Feyza; Karaca, Turan; Cemek, Mustafa; Ayaz, Ahmet; Demirtas, Selim (W B SAUNDERS CO-ELSEVIER INC, 2015)
Background/purpose: The goal of this study was to evaluate effects of exogenous sphingosylphosphorylcholine (SPC) administration on acute lung injury induced by pulmonary contusion in rats. Methods: Eight animals were included in each of the following five groups: control, contusion, contusion phosphate-buffered solution (PBS), contusion SPC 2, contusion SPC 10. SPC was administered 3 days at a daily two different doses of 2 mu m/ml and 10 mu m/ml intraperitoneally. The severity of lung injury was determined by the neutrophil activation and histological and immunohistochemical changes in the lung. Malondialdehyde (MDA), nitric oxide (NO), superoxide dismutase (SOD), glutathione peroxidase (GPx) and glutathione (GSH) were determined to evaluate the oxidative status in the lung tissue. Results: Treatment with 2 mu M SPC inhibited the increase in lung MDA and NO levels significantly and also attenuated the depletion of SOD, GPx, and GSH in the lung injury induced by pulmonary contusion. These data were supported by histopathological findings. The inducible nitric oxide synthase (iNOS) positive cells and apoptotic cells in the lung tissue were observed to be reduced with the 2 mu M SPC treatment. But, the 10 mu M SPC treatment did not provide similar effects. Conclusions: In conclusion, these findings suggested that 2 mu M SPC can attenuate lung damage in pulmonary contusion by prevention of oxidative stress, inflammatory process and apoptosis. All these findings suggest that low dose SPC may be a promising new therapeutic agent for acute lung injury. (C) 2015 Published by Elsevier Inc.
Keywords: SPC; Acute lung injury; Pulmonary contusion; Oxidative stress; Lipid peroxidation; Nitric oxide; BLUNT CHEST TRAUMA; PROTEIN-KINASE-C; SMOOTH-MUSCLE CONTRACTION; ENDOTHELIAL-CELLS; NITRIC-OXIDE; APOPTOSIS; MODEL; SPHINGOSINE-1-PHOSPHATE; INVOLVEMENT; GLUTATHIONE; Pediatrics; Surgery